Immunomodulatory and anti-inflammatory effects of hydro-ethanolic extract of Ocimum basilicum leaves and its effect on lung pathological changes in an ovalbumin-induced rat model of asthma - Naima Eftekhar; Ali Moghimi; Nema Mohammadian Roshan; Saeideh Saadat; Mohammad Hossein Boskabady (BMC, 2019)
Abstract Background Ocimum species (Lamiaceae) has been traditionally used for treatment of upper respiratory tract infections, bronchitis, coughs, sore throat, and wound healing. The Immunomodulatory and anti-inflammatory effects of hydro-ethanolic extract of Ocimum basilicum (O. basilicum) leaves was examined in ovalbumin sensitized animals. Methods Wistar rats were divided to six groups; non-sensitized, sensitized to ovalbumin, sensitized and treated with dexamethasone (1.25 μg/mL), and O. basilicum extract (0.75, 1.50 and 3.00 mg/mL) in drinking water for 21 days. The levels of interleukin 4 (IL-4), interferon gamma (IFN-γ), IFN-γ/IL-4 ratio, immunoglobulin E (IgE), phospholipase A2 (PLA2) and total protein (TP) in BALF, and lung pathological changes were examined. Results A significant increase in IL-4, IgE, PLA2 and TP levels, all lung pathological indices as well as significant decrease in IFN-γ/IL-4 ratio was seen in the asthmatic compared to the control rats (P < 0.05 to P < 0.001). Treatment with O. basilicum extract resulted in decreased IL-4, IgE, PLA2 and TP levels, but increased IFN-γ/IL-4 ratio compared to untreated sensitized rats (P < 0.01 to P < 0.001). The plant significantly improved the pathological changes of sensitized rats (P < 0.05 to P < 0.01). The improvement effects of higher concentrations of the O. basilicum extract were significantly more than those of dexamethasone (P < 0.05 to P < 0.001). Conclusion The improvement effects of O. basilicum on pathological changes, immunological and inflammatory markers in sensitized rats comparable or even more potent than dexamethasone suggests the therapeutic potential of the plant in asthma.